Detection of fake identities on twitter using supervised machine learning - Rahman, MD. Takiur; Likhon, Ataul Mim; Rahman, A. S. M Mus qur; Choudhury, Mihadul H. (BRAC University, 2019)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2019.